(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Tuberculosis (TB) has been a serious health threat worldwide, particularly in developing nations, representing high mortality as well as morbidity. The mounting incidence of multidrug-resistant tuberculosis (MDR-TB) has added complexities to TB management, requiring intensive therapy regimens leading to Adverse Drug Reactions (ADRs). ADRs influence the emergence of drug-resistant strains, by challenging treatment completion and adherence. This organised literature review consolidates observations from 12 studies, investigating ADRs in anti-tubercular therapy (ATT) and exploring how pharmacovigilance supports ADR management. Methods The analysis systematically evaluated 12 peer-reviewed studies from 2017 to 2019, focusing on articles with ADRs linked to both first-line as well as second-line TB treatment, patient outcomes with MDR-TB treatment, and pharmacovigilance’s role in ADR monitoring, across different Indian regions. Results The results emphasized excessive ADR incidence, with common ones like gastrointestinal disturbances, skin reactions, ototoxicity and hepatotoxicity, significantly hindering adherence to treatment, and causing higher incidence of incomplete therapies and patient defaulters. Various studies detailed the effectiveness of pharmacovigilance efforts in managing and identifying ADRs, promoting better patient outcomes, thereby lowering MDR-TB development risks. Conclusion ADRs continue to be a substantial obstacle for successfully treating TB, especially MDR-TB. Proactive ADR management through pharmacovigilance is essential for prompt detection of ADRs, achieving successful therapy outcomes and preventing treatment resistance. The systematic review concludes the essential role of Pharmacovigilance being integrated into TB programs, especially in high-burden and resource-limited settings, to mitigate the adverse effects of antitubercular drugs and improve overall treatment success. BJMS, Vol. 24 No. 04 October’25 Page : 1079-1092